Digestibility and digestible and metabolizable energy of corn gluten, hominy feed and wheat by-product in guinea pigs (Cavia porcellus) - Hidalgo L., Víctor (2020)
The aim of this study was to determine the digestibility of dry matter and the digestible and metabolizable energy of the wheat by-product, corn germ and hominy feed by the in vivo digestibility test in guinea pigs, using the technique of total faeces and urine collection. Genetically improved young male guinea pigs (n=15) were distributed in three groups and fed with three diets: a) Basal diet (100% wheat by-product, protected vitamin C and water), b) Mixture I (70% corn germ and 30% basal diet) and Mixture II (70% hominy feed and 30% basal diet). The nutritional values of the diets were determined. The digestibility of corn germ, hominy feed and wheat by-product were 79.0, 81.2 and 65.3%, respectively, digestible energy was 4189, 4372 and 2801 kcal/kg of dry matter, respectively, and metabolizable energy was 3910, 4351 and 2705 kcal/kg of dry matter, respectively.